1970
DOI: 10.1002/pol.1970.150081014
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanate–catalyst and hydroxyl–catalyst complex formation

Abstract: synopsisAs part of an investigation for evidence of isocyanate-catalyst and alcohol-catalyst complex formations, determinations of molecular weights were made by means of the freezing point depression of benzene solutions. Mixtures of 1-methoxy-2propanol and dibutyltin dilaurate and mixtures of 1-methoxy-%propano1 and triethylamine both gave strong evidence of the formation of complexes. Complex formations were also detected when the alcohol was replaced by phenyl isocyanate. Significantly larger concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…It is commonly accepted that urethane formation results from the activation of one or both reactants (isocyanate and hydrogen‐containing compound) by a species that contains the metal center. Of two possible reaction paths, one is a Lewis acid mechanism in which the isocyanate is firstly activated by coordination to the metal via oxygen or nitrogen atom44, 45 followed by the nucleophilic attack of the hydroxyl group from the alcohol;46 the other is the prior activation of the alcohol by the metal catalyst, followed by the complexation to the isocyanate 47…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly accepted that urethane formation results from the activation of one or both reactants (isocyanate and hydrogen‐containing compound) by a species that contains the metal center. Of two possible reaction paths, one is a Lewis acid mechanism in which the isocyanate is firstly activated by coordination to the metal via oxygen or nitrogen atom44, 45 followed by the nucleophilic attack of the hydroxyl group from the alcohol;46 the other is the prior activation of the alcohol by the metal catalyst, followed by the complexation to the isocyanate 47…”
Section: Resultsmentioning
confidence: 99%
“…For four series of reactions with different reagent concentrations, we have log R 04 ϭ log k ϩ nЈ log͓NCO͔ 04 ϩ hЈ log͓OH͔ 04 ϩ d log͓DBTDL͔ 04 (19) log R 05 ϭ log k ϩ nЈ log͓NCO͔ 05 ϩ hЈ log͓OH͔ 05 ϩ d log͓DBTDL͔ 05 (20) log R 06 ϭ log k ϩ nЈ log͓NCO͔ 06 ϩ hЈ log͓OH͔ 06 ϩ d log͓DBTDL͔ 06 (21) log R 07 ϭ log k ϩ nЈ log͓NCO͔ 07 ϩ hЈ log͓OH͔ 07 ϩ d log͓DBTDL͔ 07 (22) In this experiment, four series of reaction conditions, as shown in (k ϭ 1, 2) are known, after determining the initial reaction rates R 01 , R 02 , and R 03 , and R 04 , reaction orders h', n', and d can be computed. Following the same method as that developed for the study of a noncatalyzed system, the NCO concentration changes as a function of reaction time for each reaction system was measured, and [NCO] as a function of time (Figure 4) was determined.…”
mentioning
confidence: 99%
“…It was later found that metals can complex with isocyanate,27, 29–33 with alcohol,27, 32, 34–39 and with both isocyanate and alcohol 27, 28, 31. For example, Reegen and Frisch,32 who were studying isocyanate–DBTDL and 1‐methoxy‐2‐propanol–DBTDL complex formation in benzene solutions, concluded that DBTDL could complex with both isocyanate and alcohol, the fraction of the catalyst involved in the isocyanate complexes being significantly larger (40–50% of the DBTDL molecules being tied up in those complexes) than in complexes with alcohol (13–21% of the DBTDL molecules). They postulated the structure of the binary tin complex with 1‐methoxy‐2‐propanol, isocyanate, and bridge‐type ternary complexes of various structures.…”
Section: Resultsmentioning
confidence: 99%